2021
DOI: 10.20302/nc.2021.30.1
|View full text |Cite
|
Sign up to set email alerts
|

Endemic plants in the flora of Shutman (Sharri Mountain), Kosovo – an analysis of phytogeographical elements and life forms

Abstract: This paper aims to present the diversity of endemic plants in the Shutman area and an analysis of chorological groups and life forms. The flora of Shutman comprises 31 endemic plant species. Among them, there are 20 Balkan endemics, 1 stenoendemic and 5 sub-endemic species. They belong to 20 genera and 13 families. The richest among the endemics are families Asteraceae and Caryophyllaceae, both with 4 species. All endemics are herbaceous perennials. Hemicryptophytes dominate among life forms, accounting for 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The genetic distinction, calculated based on sequencing of the barcode region of the cytochrome c oxidase subunit I gene (COI) between Potamophylax humoinsapiens sp. n. and other of Potamophylax winneguthi Species Group, was found to be on par with those of the other morphologically recognised species in the group and especially the other five species of the P. winneguthi Species Cluster ( Ibrahimi et al 2021, Ibrahimi et al 2022. These molecular analysis showed that the closest species to Potamophylax humoinsapiens sp.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The genetic distinction, calculated based on sequencing of the barcode region of the cytochrome c oxidase subunit I gene (COI) between Potamophylax humoinsapiens sp. n. and other of Potamophylax winneguthi Species Group, was found to be on par with those of the other morphologically recognised species in the group and especially the other five species of the P. winneguthi Species Cluster ( Ibrahimi et al 2021, Ibrahimi et al 2022. These molecular analysis showed that the closest species to Potamophylax humoinsapiens sp.…”
Section: Discussionmentioning
confidence: 85%
“…For comparative assessments of morphological features of Potamophylax humoinsapiens sp. n., we used specimens of Potamophylax juliani Kumanski, 1999, Potamophylax winneguthi Malicky, 1999(in Kumanski and Malicky 1999, Potamophylax idliri Ibrahimi, Bilalli & Kucinic, 2022(in Ibrahimi et al 2022 and Potamophylax coronavirus Ibrahimi, Bilalli & Vitecek, 2021(in Ibrahimi et al 2021, collected in Osogovo Mountain in Bulgaria, Zlatibor Mountain in Serbia, Jastrebac Mountains in Serbia and Bjeshkët e Nemuna in Kosovo, accordingly. For the lacking species, comparative assessment was done, based on literature (Kumanski and Malicky 1999, Malicky 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Located between China in the northwest and Turkey in the east; Kazakhstan in the north, and the Arabian Peninsula in the south -Central Asia is rich in bluegrass, cabbage, legumes, saxifrage, stonecrop, borage, and lily families in the steppe zone. Mountain vegetation is represented by pine, deciduous-pine forests in combination with herbaceous and shrubby vegetation (Halilaj et al, 2021).…”
Section: Resultsmentioning
confidence: 99%